Nasopharyngeal Microbiome Composition is Different Among Children with Bronchial Asthma - Christine W.S. Basanti; Magd A. Kotb; Amal M. Sayed; May Abdelfattah; Mohamed Ghanem; Azza K. Abdelmegeid (Cairo University, Faculty of Medicine, Department of Pediatrics, 2021)
substantially over time. A stable microbiome is essential for immune development, while dysbiosis in the microbiome has been associated with an increased risk for asthma and allergies. Knowledge about nasopharyngeal microbiome among Egyptian children with asthma is lacking. Aim of the work: To study the nasopharyngeal microbiome in a group of Egyptian asthmatic children, and to compare it to a group of healthy controls of similar age and sex distribution. Subjects and Methods: A cross-sectional case-control study was performed on 60 Egyptian children aged 1-13 years. Of those, 30 children suffered un-exacerbated asthma, and 30 children were healthy controls. Nasopharyngeal swabs were obtained from all participants and the nasopharyngeal microbiome was identified using the VITEK 2 system after primary organism isolation by routine cultures. Results: A statistically significant difference was found for the overall microbiome composition between asthmatic and control children (p=0.007). The most common combination of organisms in asthmatics was Staphylococcus aureus and Streptococcus pneumoniae, and was statistically higher than in controls (0.038). Normal controls had a higher incidence of presence of coagulase negative staphylococci (30%) than the asthmatic group (3.3%) (p-0.009). Kocuria rosea, although present more in asthmatics, the difference did not reach statistical significance. However, within the asthmatic group, the presence of K. rosea was noted more in patients with more severe asthma (p=0.02). Conclusion: The microbiome composition in a group of asthmatic Egyptian children was different from that of healthy controls. Whether this difference has a causative relation to asthma development /severity, or is due to upregulation of certain species to combat certain environmental hazards was beyond the scope of this study and awaits further research.